1978
DOI: 10.1128/jb.136.2.465-476.1978
|View full text |Cite
|
Sign up to set email alerts
|

In vivo regulation of glycolysis and characterization of sugar: phosphotransferase systems in Streptococcus lactis

Abstract: Two novel procedures have been used to regulate, in vivo, the formation of phosphoenolpyruvate (PEP) from glycolysis in Streptococcus lactis ML3. In the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 42 publications
8
87
0
2
Order By: Relevance
“…This exclusion of TMG can be attributed to the preferential utilization of HPr-(his)-P during translocation of glucose by the mannose-PTS [43]. In earlier studies [20,32] it was observed that TMG-6P accumulated by starved cells of S. lactis was subsequently dephosphorylated intracellularly, and efflux of free/3-galactoside occurred. It has recently been discovered that glucose (and certain other sugars) can also elicit a dramatic increase in the rate of dephosphorylation and exit of TMG from TMG-6P preloaded ceils.…”
Section: Regulation Of Tmg-6p Accumula-tion By Exclusion and Expulsionmentioning
confidence: 95%
See 3 more Smart Citations
“…This exclusion of TMG can be attributed to the preferential utilization of HPr-(his)-P during translocation of glucose by the mannose-PTS [43]. In earlier studies [20,32] it was observed that TMG-6P accumulated by starved cells of S. lactis was subsequently dephosphorylated intracellularly, and efflux of free/3-galactoside occurred. It has recently been discovered that glucose (and certain other sugars) can also elicit a dramatic increase in the rate of dephosphorylation and exit of TMG from TMG-6P preloaded ceils.…”
Section: Regulation Of Tmg-6p Accumula-tion By Exclusion and Expulsionmentioning
confidence: 95%
“…However, data obtained by enzymatic analysis [20,21], [14C]fluorography [27] and in vivo [31p]NMR spectroscopy [27,28] suggest that the establishment of the PEPpotential (Fig. 3,A and B) results from the inactivation of pyruvate kinase by: (a) depletion of positive effectors of the allosteric enzyme (e.g., FDP, [29][30][31][32]), and (b) marked increase in intracellular Pi concentration, a potent inhibitor of PK in vitro [29,31]. The presence of the PEP-potential in starved organisms is of experimental and physiological importance because: (i) it permits the characterization of PTS functions and isolation of PTS products in intact cells [20,32,33]; (ii) the slow utilization of PEP by PK may provide the necessary maintenance energy for the organism during starvation [20,26]; (iii) starved cells are 'primed' for the immediate transport of lactose and other PTS sugars when these compounds are once more available [ Fig. 3 C]; and (iv) the PEP-potential permits preloading of cells with non-metabolizable sugar (phosphate) analogs for investigations concerned with intracellular dephosphorylation and expulsion of sugars [22,34].…”
Section: Lactose Transport By Starved Cells: Role Of Pep-potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…5) (for a review on pyruvate metabolism see [3]). During homolactic fermentation, regulation of the carbon flux was associated with high levels of FBP, which activates LDH and PK, directing the flux towards the production of lactate [113,114,151]. Conversely, the formation of end-products other than lactate was rationalized as being due to the reduction of LDH activity caused by lower levels of the effector, FBP, and to the relief of pyruvate formate lyase (PFL) inhibition by the concomitant decrease of DHAP and glyceraldehyde 3phosphate [102,114].…”
Section: Shift To Mixed-acid Fermentation and The Impact Of Oxygenmentioning
confidence: 99%